The role of multidimensional social capital in crowdfunding: A comparative study in China and US - Zheng, Haichao; Li, Dahui; Wu, Jing; Xu, Yun (Information & management, 2014)
How does an entrepreneur's social network impact crowdfunding? Based on social capital theory, we developed a research model and conducted a comparative study using objective data collected from China and the U.S. We found that an entrepreneur's social network ties, obligations to fund other entrepreneurs, and the shared meaning of the crowdfunding project between the entrepreneur and the sponsors had significant effects on crowdfunding performance in both China and the U.S. The predictive power of the three dimensions of social capital was stronger in China than it was in the U.S. Obligation also had a greater impact in China.